Implementasi Light Painting Photography Dalam Analisis Cakupan Jaringan Wireless LAN Menggunakan Perangkat Berbasis Wemos D1 - Wisnu Fajar Dewantara; Sabriansyah Rizqika Akbar; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Wireless technology makes any devices can be connected without wire that limiting the range. We need an optimal placement and configuration of the access point for optimal coverage reasons. Signal strenght from access point does effect to a connection quality. Nowadays network analyst are using a network coverage analyzer software called Ekahau Heatmapper. It uses heatmap method to mapping network coverage. The software analyzes RSSI's (Received Signal Strenght Indicator) value then the value into a range. Each range is represented by color that signs the strenght of wireless signal. But its procedure should be awkward for some reason. You need to draw a sketch of the room that you want to analyze. Then you must bring your laptop to track around the room. Wi-Spec offers an alternatives with a same method based on heatmap that Ekahau Heatmapper does. Wi-Spec is a device using Wemos D1 as it's microcontroller with RGB Led Strips as output. We combine this method with light painting photography using a photo as frame makes the result is more real and accurate than info from 2D sketch that Ekahau does. Wi Spec compatible with Arduino IDE using ESP8266Wifi.h and FastLED.h. FasLED.h library features predifined color that can subtitute the heatmap color from Ekahau Heatmapper. These colors are : Green, Lime, , Yellow, Orange, Red, and running dot red light while it hasn't receive signal.. From the SSID and RSSI capability test, the device can't get the SSID and RSSI from a hidden configured SSID. Differences of wireless receivers beetween implementation caused a different result on one of an area point.